The Influence of Work Culture, Work Discipline and Job Satisfaction on The Performance of Indonesian Migrant Workers in Ishinomaki City Japan - Abdul Azis Hasan; Jaelani Jaelani (Pusat Riset dan Inovasi Nasional, 2025)
Based on a survey from the Japan External Trade Organization in 2020, 55.8 percent of Japanese companies were dissatisfied with the productivity of Indonesian workers. This shows that there are factors that influence the dissatisfaction of Japanese companies with Indonesian migrant workers. Among them are due to differences in the level of discipline, work culture and level of job satisfaction possessed by Indonesian migrant workers. The purpose of this study was to determine the effect of work culture, work discipline and job satisfaction on the performance of Indonesian migrant workers in Ishinomaki City, Japan. This research is quantitative and qualitative research with data sources from primary data. The sampling technique used a simple random sampling method using the Slovin formula as many as 80 respondents. The data analysis technique used is multiple regression analysis, t test, F test and coefficient of determination (R2) test. The results showed that work culture and work discipline had a significant effect on the performance of Indonesian migrant workers in Ishinomaki City, Japan, while job satisfaction had no significant effect on the performance of Indonesian migrant workers in Ishinomaki City, Japan.